Occurrence of Seropositivity of Toxoplasma gondii, Cytomegalovirus, and Rubella Infections in Pregnant Women - Shahida Karamat, Fiza Ali Khan, Saira Saeed, Aliya Jafri, Suresh K Langhani, Aniqa Saleem, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the seropositivity for Toxoplasma gondii, Rubella virus, and Cytomegalovirus among pregnant females in Hyderabad, Sindh, Pakistan Methodology: A prospective study was undertaken at the Department of Gynecology and Obstetrics, Bahria University of Health Sciences, Karachi, Pakistan between March 2020 to June 2021. All women with confirmed pregnancies were eligible to participate in the study. Women with ectopic pregnancy or women who were not receiving prenatal care at our center were excluded. All participants underwent assessment for antibody Titres for Toxoplasmosis, Rubella, and CMV. Blood specimens of participating women were obtained in aseptic conditions for laboratory investigations. The IgM and IgG antibodies for Toxoplasma gondii, Rubella, and CMV along with IgG antibodies for CMV and Toxoplasma gondii were assessed comprehensively. Seropositivity was stratified with respect to age groups. Results: A total of 336 women with a mean age of 26.88 ± 3.77 years were included. The rate of seropositivity for anti-Toxoplasma IgM, anti-Rubella IgM, and anti-CMV IgM was 1.2%, 0.6%, and 2.7%, consecutively. A total of four (1.2%) cases were positive for anti-Toxoplasma IgM. 126(37.5%) women were positive for Anti-Toxoplasma IgG. For the three positive cases of both IgM and IgG, avidity test showed high avidity. Overall, one case for toxoplasma gondii was detected. Two women were positive for anti-Rubella IgM only (positive cases). Overall, 291 (86.6%) individuals were positive for Rubella IgG. Overall, two cases of Rubella were detected in our study. All nine positive cases of anti-CMV IgM antibodies were also positive for anti-CMV IgG. For these nine cases, anti-CMV IgG avidity was reported which turned out to be intermediary or high. Overall, we did not detect a case of CMV in our study. Conclusion: We found high levels of IgG antibodies for Rubella and CMV, indicating past infection/immunity. The present study highlighted the seroprevalence rate of Toxoplasma gondii, CMV, and Rubella in a cohort of pregnant women from Sindh. However, this rate could be under-reported as many women do not avail of antenatal services during pregnancy, especially from rural Sindh, Pakistan. Nevertheless, this study adds to the current literature. Furthermore, it is recommended to regularly screen pregnant females for these infections. Keywords: Cytomegalovirus, rubella, seroprevalence, torch infections, toxoplasma gondii